Die persoon van vrede in die sending - P. Verster (Acta Theologica)
The concept of the “person of peace” plays an important role among evangelicals. To reach a community, such a “person of peace” is often identified. This person can then expose the community to mission. From a theological perspective it is possible to acknowledge the importance of such a “person of peace”. In this instance the concept should be expanded to include the notion of the church’s task to bring about peace. This peace must visibly elicit people in need to bring about harmony in all spheres of life.